Saturday, December 17, 2011

Notes on classical sequent calculi (1/2)

These are some notes I made to try to help me understand Noam's focused presentation of classical logic in Polarity and the Logic of Delimited Continuations. I hope these notes coud be useful to others.

Sequent presentations of classical logic

I write, inevitably, from the perspective of an intuitionistic proof theorist, so let's start there. In intuitionistic logics, sequents have the form \(\Gamma \vdash A~\mathit{true}\), where the hypothetical context \(\Gamma\) has the form \(A_1~\mathit{true}, \ldots, A_n~\mathit{true}\). The whole sequent \(\Gamma \vdash A~\mathit{true}\) is read as "assuming the truth of all the things in \(\Gamma\), we know \(A~\mathit{true}\)." Let's look at a couple of ways of presenting sequent calculi for classical logic.

Two-sided judgmental classical sequent calculi

One way of presenting a classical sequent calculus is to give a two-sided sequent, \(\Gamma \vdash \Delta\). As before, \(\Gamma\) has the form \(A_1~\mathit{true}, \ldots, A_n~\mathit{true}\), but \(\Delta\) has the form \(B_1~\mathit{false}, \ldots, A_m~\mathit{false}\), and the whole sequent is read as "taken together, if all the things judged true in \(\Gamma\) are true and all the things judged false in \(\Delta\) are false, then there is a contradiction."

The language of propositions is \(A ::= P \mid \neg A \mid A \wedge B \mid A \vee B\) - uninterpreted atomic propositions \(P\), negation, conjunction ("and"), and disjunction ("or"). I'm leaving out truth \(\top\) and falsehood \(\bot\) because they're boring. The rules for these two-sided classical sequent calculi look like this:

\[ \infer {\Gamma, ~ P~\mathit{true} \vdash \Delta, ~ P~\mathit{false}} {} \] \[ \infer {\Gamma \vdash \Delta, ~ \neg A~\mathit{false}} {\Gamma, ~ A~\mathit{true} \vdash \Delta} \qquad \infer {\Gamma, ~ \neg A~\mathit{true} \vdash \Delta} {\Gamma \vdash \Delta, ~ A~\mathit{false}} \] \[ \infer {\Gamma \vdash \Delta, ~ A \wedge B~\mathit{false}} {\Gamma \vdash \Delta, ~ A~\mathit{false} &\Gamma \vdash \Delta, ~ B~\mathit{false}} \qquad \infer {\Gamma, ~ A \wedge B~\mathit{true} \vdash \Delta} {\Gamma, ~ A~\mathit{true}, ~ B~\mathit{true} \vdash \Delta} \] \[ \infer {\Gamma \vdash \Delta, ~ A \vee B~\mathit{false}} {\Gamma \vdash \Delta, ~ A~\mathit{false}, ~ B~\mathit{false}} \qquad \infer {\Gamma, ~ A \vee B~\mathit{true} \vdash \Delta} {\Gamma, ~ A~\mathit{true} \vdash \Delta &\Gamma, ~ B~\mathit{true} \vdash \Delta} \]

Two asides. First, in presentations that do not emphasize the fact that \(A_i~\mathit{false}\) and \(B_j~\mathit{true}\) are judgments and not propositions, there is another reading of the two-sided sequent \[A_1,\ldots,A_n \vdash B_1,\ldots,B_m\] This interpretation is that the truth of all of the \(A_i\) implies the truth of one of the \(B_j\) - this reading suggests a reading of any intuitionistic sequent proof as a classical sequent proof with one conclusion. You should convince yourself that this interpretation is equivalent to the interpretation above (hint: it's just a mode of use of De Morgan's laws).

Second aside: your rules may differ. I'm using a style of presentation where every connective is broken down by a unique connective and, from the perspective of bottom-up proof search, it's never a mistake to apply any rule, because the conclusion implies all of the premises (a property called invertibility). The "true" (or left) rule for conjunction (that is, "and" or \(\wedge\)) and the "false" (or right) rule for disjunction (that is, "or" or \(\vee\)) both have a different, non-invertible presentation. In the case of conjunction, it's this pair of rules: \[ \infer {\Gamma, ~ A \wedge B~\mathit{true} \vdash \Delta} {\Gamma, ~ A~\mathit{true} \vdash \Delta} \qquad \infer {\Gamma, ~ A \wedge B~\mathit{true} \vdash \Delta} {\Gamma, ~ B~\mathit{true} \vdash \Delta} \] You could "make a mistake" applying these rules in bottom-up proof search: just because there is a proof of \(\Gamma, ~ A \wedge B~\mathit{true} \vdash \Delta\) does not mean that there is a proof of \(\Gamma, ~ A~\mathit{true} \vdash \Delta\).

One-sided judgmental sequent sequent calculi

Of course, hypotheses are just hypotheses, there's no a priori reason why we need to separate the true ones and the false ones into separate contexts. Let's use a unified context and call it \(\Psi\). \[\Psi ::= \cdot \mid \Psi, A~\mathit{true} \mid \Psi, A~\mathit{false}\] Then, we can have the sequent form \(\Psi \vdash \#\), which we read as "all the assumptions in \(\Psi\) together imply a contradiction" - we pronounce \(\#\) as "contradiction." We'll need rewrite all of our rules:

\[ \infer {\Psi, ~ P~\mathit{true}, ~ P~\mathit{false} \vdash \#} {} \] \[ \infer {\Psi, ~ \neg A~\mathit{false} \vdash \#} {\Psi, ~ A~\mathit{true} \vdash \#} \qquad \infer {\Psi, ~ \neg A~\mathit{true} \vdash \#} {\Psi, ~ A~\mathit{false} \vdash \#} \] \[ \infer {\Psi, ~ A \wedge B~\mathit{false} \vdash \#} {\Psi, ~ A~\mathit{false} \vdash \# &\Psi, ~ B~\mathit{false} \vdash \#} \qquad \infer {\Psi, ~ A \wedge B~\mathit{true} \vdash \#} {\Psi, ~ A~\mathit{true}, ~ B~\mathit{true} \vdash \#} \] \[ \infer {\Psi, ~ A \vee B~\mathit{false} \vdash \#} {\Psi, ~ A~\mathit{false}, ~ B~\mathit{false} \vdash \#} \qquad \infer {\Psi, ~ A \vee B~\mathit{true} \vdash \#} {\Psi, ~ A~\mathit{true} \vdash \# &\Psi, ~ B~\mathit{true} \vdash \#} \]

Hopefully you'll agree that this is "obviously the same" as the first presentation.

One-sided, truth-oriented sequent calculi

But wait! The "false" rule for conjunction looks just like the "true" rule for disjunction, and the "true" rule for conjunction looks just like the "false" rules for disjunction. Can we simplify these rules?

The usual answer is that you can, indeed, do with fewer rules and without a false judgment at all. However, we need two twists to deal with the rules that involved both the true and false judgments. First, we need to let every atomic proposition come in two flavors, the "regular" flavor \(P\) and the "negated" flavor \(\overline{P}\). Then, the rule dealing with atomic propositions looks like this: \[ \infer {\Gamma, ~ P~\mathit{true}, ~ \overline{P}~\mathit{true} \vdash \#} {} \] Second, instead of negation being a proposition \(\neg A\), we define a negation function, which I will write as \((A)^\bot\) to distinguish it from the propositional negation \(\neg A\). W. The negation function is defined as follows: \[ \begin{align} {(P)^\bot} = & \overline{P}\\ {(\overline{P})^\bot} = & P\\ {(A \wedge B)^\bot} = & {(A)^\bot} \vee {(B)^\bot}\\ {(A \vee B)^\bot} = & {(A)^\bot} \wedge {(B)^\bot}\\ \end{align} \] With this definition, we can eliminate the negation proposition altogether - the negation function just applies De Morgan laws all the way down to atomic propositions. We now get our sequent calculus for "half off" - there's no more official negation, and we don't need the false judgment at all anymore. We only need two more rules (for a total of three)!

\[ \infer {\Psi, ~ A \wedge B~\mathit{true} \vdash \#} {\Psi, ~ A~\mathit{true}, ~ B~\mathit{true} \vdash \#} \qquad \infer {\Psi, ~ A \vee B~\mathit{true} \vdash \#} {\Psi, ~ A~\mathit{true} \vdash \# &\Psi, ~ B~\mathit{true} \vdash \#} \]

It would also be possible to play this game the other way around: gather everything on the right-hand side, bias the whole thing towards the "false" judgment, and basically get the "other half" of the two-sided sequent calculi. This ability to play the game equally well either way is part of what people mean when they say that classical logic is "very symmetric."

However, given that it's all the same, why not reason about truth and not falsehood? I've never understand why classical linear logic (in particular) always seems to bias itself towards one-sided sequent calculi on the right. There are important differences in what it means to think like a classical linear logician and what it means to think like an intuitionistic linear logician, but I really think that it unnecessarily exacerbates this divide when we have to turn all of our \(\oplus\)es to \(\&\)s and \(\otimes\)es to pars in order to talk to one another.

Polarized presentations of classical logic

Now for the real purpose of this note: writing out the review of classical logic that Noam gives in "Polarity and the Logic of Delimited Continuations." This discussion is a synthesis of that presentation and a little bit of "On the unity of duality."

Two for the price of two

Fundamentally, the observation Noam is making is that the one-sided truth-oriented sequent calculus goes too far - really, there are two kinds of disjunction, and two kinds of conjunction, which is why it seemed like the original calculus seemed to have redundancies. The third system above (the one-sided, truth-oriented sequent calculus) made it look like we were getting our logic for "half-off" - but really that's because the first two judgmental presentations were defining twice as many connectives as appeared to the naked eye. (As an aside, if you study classical linear logic, you're forced into the same conclusion for different reasons.)

Jason Reed taught me that, if you have two different judgments in a logic, it's worth seeing what happens if you syntactically differentiate the things you judge to be true and the things you judge to be false. Let's go ahead and "guess the right answer" - I'm going to call the things we judge to be true positive, and that the things we judge to be false negative. There's more than one of everything! \[ \begin{align} A^- = & \neg^- A^+ \mid P^- \mid A^- \wedge^- B^- \mid A^- \vee^- B^-\\ A^+ = & \neg^+ A^- \mid P^+ \mid A^+ \wedge^+ B^+ \mid A^+ \vee^+ B^+ \end{align} \] Here are a bunch of rules: note that the fact that the two negations change the polarity of the propositions; the rules make it evident that this is the right thing to do, because we have (for example) \(\neg^+ A^- ~\mathit{true}\) but \(A^- ~\mathit{false}\):

\[ \infer {\Psi, ~ \neg^- A^+~\mathit{false} \vdash \#} {\Psi, ~ A^+~\mathit{true} \vdash \#} \qquad \infer {\Psi, ~ \neg^+ A^-~\mathit{true} \vdash \#} {\Psi, ~ A^-~\mathit{false} \vdash \#} \] \[ \infer {\Psi, ~ A^- \wedge^- B^-~\mathit{false} \vdash \#} {\Psi, ~ A^-~\mathit{false} \vdash \# &\Psi, ~ B^-~\mathit{false} \vdash \#} \qquad \infer {\Psi, ~ A^+ \wedge^+ B^+~\mathit{true} \vdash \#} {\Psi, ~ A^+~\mathit{true}, ~ B^+~\mathit{true} \vdash \#} \] \[ \infer {\Psi, ~ A^- \vee^- B^-~\mathit{false} \vdash \#} {\Psi, ~ A^-~\mathit{false}, ~ B^-~\mathit{false} \vdash \#} \qquad \infer {\Psi, ~ A^+ \vee^+ B^+~\mathit{true} \vdash \#} {\Psi, ~ A^+~\mathit{true} \vdash \# &\Psi, ~ B^+~\mathit{true} \vdash \#} \]

So, are we good? Well, no, not really. The problem is that the "+" or "-" stuck to an atomic proposition isn't an annotation or modifier the way the overbar was in the one-sided, truth-oriented sequent calculus above. \(P^+\) and \(P^-\) are different atomic propositions, and it wouldn't be right to given an inference rule that had, as its conclusion, \(\Psi, ~ P^+~\mathit{true}, ~ P^-\mathit{false}\). Why? Well, for now let's go with "because I said so." The argument I have for this point isn't bulletproof, and it has to do with the role of atomic propositions as stand-ins for other propositions.

However, if you accept my argument from authority, we are left no way to prove, or even to state, anything equivalent to the classical \(P \vee \neg P\) into polarized logic, since any way we try to polarize this formula will lead to \(P\) needing to be both positive and negative. We're going to need some way, different from negation, of including positive propositions in negative ones.

These inclusions of positive propositions into negative ones (and vice versa) are called shifts - \({\downarrow}A^-\) is a positive proposition and \({\uparrow}A^+\) is a negative proposition. We could just add these two rules and call it a day... \[ \infer {\Psi, ~ P^+~\mathit{true}, ~ {\uparrow}P^+~\mathit{false} \vdash \#} {} \qquad \infer {\Psi, ~ P^-~\mathit{false}, ~ {\downarrow}P^-~\mathit{true} \vdash \#} {} \] ...but this is hardly general: the rules above should be derivable; this rule should be derivable as well: \[ \infer {\Psi, ~ P^+~\mathit{true}, ~{\uparrow}(P^+ \vee^+ Q^+)~\mathit{false} \vdash \#} {} \] All three of these derivable rules share a common property: in an on-paper proof, we would say that the contradiction is "trivial." The hypothesis \({\uparrow}P^+~\mathit{false}\) is trivial due to the fact that \(P^+\) is true by a different hypothesis, and because the truth of \(P^+\) allows us to trivially conclude that \(P^+ \vee^+ Q^+\) is true, \(P^+ \vee^+ Q^+\) is trivially contradictory as well.

This idea is encoded in two rules which capture proof-by-contradiction. One way we establish a contradiction is by showing that \(A^+\) is both false (by assumption) and trivial (by direct proof). The other way we establish a contradiction is by showing that \(A^-\) is both true (by assumption) and false (by direct proof of absurdity). These are embodied in the following two rules:

\[ \infer {\Psi \vdash \#} {{\uparrow}A^+~\mathit{false} \in \Psi &\Psi \vdash A^+~\mathit{trivial}} \qquad \infer {\Psi \vdash \#} {{\downarrow}A^-~\mathit{true} \in \Psi &\Psi \vdash A^-~\mathit{absurd}} \]

Now, of course, we need to give a bunch more rules to describe how to prove positive propositions trivial and negative propositions absurd.

\[ \infer {\Psi, ~ P^+~\mathit{true} \vdash P^+~\mathit{trivial}} {} \qquad \infer {\Psi, ~ P^-~\mathit{false} \vdash P^-~\mathit{absurd}} {} \] \[ \infer {\Psi \vdash \neg^+ A^-~\mathit{trivial}} {\Psi \vdash A^-~\mathit{absurd}} \qquad \infer {\Psi \vdash \neg^- A^+~\mathit{absurd}} {\Psi \vdash A^+~\mathit{trivial}} \] \[ \infer {\Psi \vdash A^+ \wedge^+ B^+~\mathit{trivial}} {\Psi \vdash A^+~\mathit{trivial} &\Psi \vdash B^+~\mathit{trivial}} \qquad \infer {\Psi \vdash A^+ \vee^+ B^+~\mathit{trivial}} {\Psi \vdash A^+~\mathit{trivial}} \qquad \infer {\Psi \vdash A^+ \vee^+ B^+~\mathit{trivial}} {\Psi \vdash B^+~\mathit{trivial}} \] \[ \infer {\Psi \vdash A^- \wedge^- B^-~\mathit{absurd}} {\Psi \vdash A^-~\mathit{absurd}} \qquad \infer {\Psi \vdash A^- \wedge^- B^-~\mathit{absurd}} {\Psi \vdash B^-~\mathit{absurd}} \qquad \infer {\Psi \vdash A^- \vee^- B^-~\mathit{absurd}} {\Psi \vdash A^-~\mathit{absurd} &\Psi \vdash B^-~\mathit{absurd}} \]

Even yet, we are not done! We need to deal with the shifts, which embody another form of proof-by-contradiction: to prove that \(A^-\) holds trivially, assume it's false and derive a contradiction.

\[ \infer {\Psi \vdash {\downarrow}A^-~\mathit{trivial}} {\Psi, A^-~\mathit{false} \vdash \#} \qquad \infer {\Psi \vdash {\uparrow}A^+~\mathit{absurd}} {\Psi, A^+~\mathit{true} \vdash \#} \]

The thing that we've come up with by this process is what I've been calling a "weakly focused" version of classical logic. If we wanted to turn it into a "fully focused" presentation of classical logic, we'd only need to make one change: the first "proof by contradiction" rules, which we call "focusing" rules, would need to require that the context \(\Psi\) includes only judgments of the form \(P^+~\mathit{true}\), \({\downarrow}A^-~\mathit{true}\), \(P^-~\mathit{false}\), and \({\uparrow}A^+~\mathit{false}\). A context including only judgments of these four forms is called stable. To get full focusing, we would modify the "trivial focus" rule like this (a similar modification would be made to the "absurd focus" rule):

\[ \infer {\Psi \vdash \#} {{\uparrow}A^+~\mathit{false} \in \Psi &\Psi \vdash A^+~\mathit{trivial} &\Psi~\mathit{stable}} \]

Thinking about the sequent calculus as a bottom-up proof search procedure, if we are looking for a proof of a non-stable sequent, we can use our original, invertible rules to break down the connectives in the contexts until we have only stable sequents, at which point we can apply a focusing rule.

Until next time...

I haven't quite had time to do the thing I originally set out to do, which was to work through the notation in "Polarity and the logic of delimited continuations" better. But I will save that for another time. The motivation is the same as the one from before: it seems like we're almost certainly duplicating work. Is it possible to give the presentation of polarized classical logic from the previous section using about half as many rules?


  1. There's some typos in the line of rules for deriving absurdity of conjunction and disjunction: all the connectives should be negative, the first rule's premise should be absurd and the connective in the second rule should be a conjunction.

  2. Thanks, Rowan! I was getting a little sloppy by that point, I guess :-P. Should be fixed now.